Challenges and opportunities in data accessibility - Calva, Mónica (2022)
There is a great variety and amount of sensitive and valuable healthcare information that could be used to benefit people, but is not exploited due to limited access to data. This article aims to determine factors influencing data accessibility in private and public organizations through a literature review. Of the 300 related articles identified, 23 were included in this review. Among the resulting factors influencing information accessibility, the following stood out: open governments, health information systems, personal data protection laws, ethics in the use of medical information, and data lakes. Making health data more accessible would improve services and treatment plans, save state resources and promote education and research.